Transient neonatal hyperthyrotrophinaemia: a serum abnormality due to transplacentally acquired antibody to thyroid stimulating hormone. Issue 6365 (19th February 1983) - Lazarus, J H; John, R; Ginsberg, J; Hughes, I A; Shewring, G; Smith, B R; Woodhead, J S; Hall, R
Abstract : In a screening programme for neonatal hypothyroidism an otherwise healthy female infant was found to have a high concentration of thyroid stimulating hormone in a filter paper blood spot and in serum. A high concentration was also found in the maternal serum. Mother and baby were both biochemically euthyroid with normal serum thyroxine concentrations. The apparently high concentration of thyroid stimulating hormone in the mother was due to the presence of an IgG antibody that bound to human but not bovine thyroid stimulating hormone. Maternal serum inhibited the action of human thyroid stimulating hormone in an in vitro bioassay for the hormone. It is suggested that the baby acquired the antibody transplacentally, especially as the concentration of thyroid stimulating hormone subsequently fell. It is concluded that maternal serum should be assayed for thyroid stimulating hormone when a neonate is found to have a high concentration of the hormone and a normal concentration of thyroxine to establish the incidence of this finding and to avoid inappropriate replacement treatment.